(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In colonialist writing, Bhagat Singh has been(mis)identified as "Terrorist". However for the nationalists ofIndia, Bhagat Singh embodies "courage and sacrifice". He is none, ofthese an rebel nor a terrorist. He is an image / symbol of revolution. Aproto-socialist, a man queradicalist also a submitted secularist, he ispromethean figure with strength and conviction to undertake the forceful. Anideologue like M. K. Gandhi, he is an impeccable foil to Gandhi himself. Havinga place more to the super class of BG Tilak, Lala Lajpat Rai, Bhagat Singh is awell-suited original picture of suffering and emancipatory militarism.